Melatonin-MT1 signal is essential for endometrial decidualization. Issue 2 (12th July 2021) - Cui, Liyuan; Xu, Feng; Wang, Songcun; Jiang, Zhuxuan; Liu, Lu; Ding, Yan; Sun, Xiaoli; Du, Meirong
Abstract : Deficient decidualization of endometrial stromal cells (ESCs) can cause adverse pregnancy outcomes including miscarriage, intrauterine growth restriction, and pre-eclampsia. Decidualization is regulated by multiple factors such as hormones and circadian genes. Melatonin, a circadian-controlled hormone, is reported to be important for various reproductive processes, including oocyte maturation and placenta development. Its receptor, MT1, is considered to be related to intrauterine growth restriction and pre-eclampsia. However, the role of melatonin-MT1 signal in decidualization remains unknown. Here, we reported that decidual stromal cells from miscarriages displayed deficient decidualization with decreased MT1 expression. The expression level of MT1 is gradually increased with the process of decidualization induction in vitro . MT1 knockdown suppressed the decidualization level, while the overexpression of MT1 promoted the decidualization process. Moreover, changing MT1 level could regulate the expression of decidualization-related transcription factor FOXO1. Melatonin promoted decidualization and reversed the decidualization deficiency due to MT1 knockdown. Using in vitro and in vivo experiments, we further identified that lipopolysaccharide (LPS) could induce inflammation and decidualization resistance with downregulated MT1 expression, and melatonin could reverse the inflammation and decidualization resistance induced by LPS. These results suggested that the melatonin-MT1 signal might be essential for decidualization and might provide a novel therapeutic target for decidualization deficiency-associated pregnancy complications.